Interfacial friction behaviour in narrow wall paste backfill system - Ting, Wee Kiet; Alsidqi, Hasan; Fauzan, Sahdi; Siti Noor Linda, Taib; Norsuzailina, Mohamed Sutan; Badrulhisham, Abdul Aziz (Construction Research Institute of Malaysia (CREAM), 2018)
Understanding on the effects of interfacial friction within narrow wall is important in the design of underground stope backfill system. Laboratory scale stope model made of metal such as aluminium is normally used to simulate the actual stope paste backfill system, however, verification of such system in terms of interfacial friction behaviour is lacking. This paper presents the experimental results on the interfacial friction between backfill material and the aluminium narrow wall system as well as the internal friction of the paste backfill. Standard and modified direct shear tests are employed to investigate such behaviours under dry and saturated conditions for uncemented paste backfill (UCPB) and cemented paste backfill (CPB). For the CPB, cast in-situ and precast is also compared. The shear stress-strain behaviour is showcased in detail for every test. The general findings show that the interfacial friction angle (δ) at the backfill-aluminium interface is weaker than internal friction angle (ϕ) of the backfill itself with an average factor of 0.69 (δ/ϕ =0.69). This factor is comparable to 2/3 or 0.67 which is commonly used in the design and analyses. The results help to better understand the behaviour of the backfill system, enabling engineers to optimize the paste backfill system design.